2011
DOI: 10.1002/asna.201111560
|View full text |Cite
|
Sign up to set email alerts
|

The Bar and Spiral Structure Legacy (BeSSeL) survey: Mapping the Milky Way with VLBI astrometry

Abstract: Astrometric Very Long Baseline Interferometry (VLBI) observations of maser sources in the Milky Way are used to map the spiral structure of our Galaxy and to determine fundamental parameters such as the rotation velocity (Θ0) and curve and the distance to the Galactic center (R0). Here, we present an update on our first results, implementing a recent change in the knowledge about the Solar motion. It seems unavoidable that the IAU recommended values for R0 and Θ0 need a substantial revision. In particular the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
192
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(196 citation statements)
references
References 65 publications
4
192
0
Order By: Relevance
“…The ratio of Θ 0 /R 0 has been well constrained to be 29.4 ± 0.9 km s −1 kpc −1 . Brunthaler et al (2011) suggested a value of Θ 0 = 239 ± 7 km s −1 . Schönrich (2012) obtained R 0 = 8.27 ± 0.29 kpc and Θ 0 = 238 ± 9 km s −1 by analyzing the stellar kinematics.…”
Section: Fundamental Parameter R 0 θ 0 and Solar Motionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ratio of Θ 0 /R 0 has been well constrained to be 29.4 ± 0.9 km s −1 kpc −1 . Brunthaler et al (2011) suggested a value of Θ 0 = 239 ± 7 km s −1 . Schönrich (2012) obtained R 0 = 8.27 ± 0.29 kpc and Θ 0 = 238 ± 9 km s −1 by analyzing the stellar kinematics.…”
Section: Fundamental Parameter R 0 θ 0 and Solar Motionsmentioning
confidence: 99%
“…Based on the stellar kinematics in the solar neighborhood, Schönrich et al (2010) revised the solar motions with respect to the Local Standard of Rest (LSR) as U = 11.10 km s −1 (radially inward), V = 12.24 km s −1 (in the direction of Galactic rotation), and W = 7.25 km s −1 (vertically upward, all in J2000), which are inherently incorporated in the LSR velocities of spiral tracers, hence influence the estimation of their kinematic distances. A consistent value of the distance of the Sun to the Galactic center (GC), R 0 = 8.3 kpc, was proposed by Brunthaler et al (2011), who incorporated studies on stellar orbits in the GC (Ghez et al 2008;Gillessen et al 2009) and trigonometric parallax measurements toward Sgr B2 ) and massive star forming regions (Reid et al 2009b;Brunthaler et al 2011). The circular rotation of the LSR, Θ 0 , was estimated to be 239 km s −1 .…”
Section: Introductionmentioning
confidence: 96%
“…However, there are only a few maser parallax measurements, and current efforts to increase their number (e.g. BeSSeL project, Brunthaler et al 2011) are naturally focused on high-mass star forming regions, more prone to maser emission. Therefore, very few of our fields have known maser emission, and none of …”
Section: Determination Of Distancesmentioning
confidence: 99%
“…Similar observations have been made using the European very-long base-line radio interferometer [66], which includes three Russian antennas: Svetloe, Zelenchukskaya, and Badary. At present, these two programs are combined in the BeSSeL 5 (Bar and Spiral Structure Legacy Survey, Brunthaler, et al [67]). Radio observations of water masers at 22.2 GHz [68] are being carried out in the Japanese program VERA (VLBI Exploration of Radio Astronomy).…”
Section: H2 Molecular Clouds and Hii Zonesmentioning
confidence: 99%